Bio-fuel crops research for energy security and rural development in developing countries - Reddy, B.V.S.; Ramesh, S; Kumar, A.; Wani, S.P.; Ortíz, R.; Sreedevi, TK (Springer, 2008)
Soaring prices of fossil fuels, geo-political issues and environmental pollution associated with fossil fuel use has led to worldwide interest in the production and use of bio-fuels. Both the developed and developing countries have developed a range of policies to encourage production of combustible fuels from plants that triggered public and private investments in bio-fuel crop research and development, and bio-fuels production. In this article, we discuss the potential benefits of bio-fuels in increasing the farmers’ incomes, reducing environment pollution, the crop options and research and development interventions required to generate feedstocks to produce bio-fuels to meet projected demand without compromising food/fodder security in developing countries.